Trafficking Rhetoric Race, Migration, and the Making of Modern-Day Slavery - Hill, Annie (The Ohio State University Press, 2024)
"Human trafficking has generated intense global concern, with stories of sex slavery and images of women forced into prostitution so persuasive that states have raced to respond ahead of empirical data and clear definitions of the crime. In Trafficking Rhetoric, Annie Hill analyzes the entanglement of state veneration and state violence by tracking how the United Kingdom points to the alleged crimes of others in order to celebrate itself and conceal its own aggression. Hill compares the UK$1 (Bs acclaimed rescue approach to human trafficking with its hostile approach to migration, arguing that they are two sides of the same coin$1 (Bone that relies on rhetorical constructions of (3z(Btrafficked women(3y (Band (3z(Billegal migrants(3y (Bto materialize the UK as an Anglo-white space.Drawing from official estimates, policy papers, NGO reports, news stories, and awareness campaigns and situating them in the broader EU context, Hill accounts for why the UK$1 (Bs antitrafficking agenda emerged with such rhetorical force in the early twenty-first century. Trafficking Rhetoric reframes controversies over labor, citizenship, and migration while challenging the continued traction of race-baiting and gender bias in determining who has the right to live, work, and belong in the nation."s
English
Keywords: Sociology; Semantics, discourse analysis, etc; Gender studies: women; Social Science; Sociology; Language Arts & Disciplines; Rhetoric; Social Science; Women's Studies